2014
DOI: 10.1007/s10549-014-3022-7
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring patient-centered outcomes through the progression of breast reconstruction: a multicentered prospective longitudinal evaluation

Abstract: Studies have shown that having breast reconstruction has a positive influence on patient satisfaction and health-related quality of life (HRQoL) at the conclusion of treatment. However, no study has critically evaluated changes to these patient-reported outcomes during the process of undergoing breast reconstruction. This study was to prospectively evaluate changes to patient-centered metrics through the progression of breast reconstruction. An IRB-approved prospective, multi-institutional study was performed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
36
1
6

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 72 publications
(44 citation statements)
references
References 17 publications
1
36
1
6
Order By: Relevance
“…In one of the earliest studies using the BREAST-Q to examine the differences in PROs between women undergoing mastectomy alone versus reconstruction, Eltahir et al demonstrated lower BREAST-Q scores for Satisfaction with Breasts, Psychosocial Well-being, and Sexual Well-being in women after mastectomy alone versus mastectomy with reconstruction (23). These findings have been replicated in multiple subsequent studies (19, 20, 24, 25), including a prospective study by Chao et al that demonstrated lower Satisfaction with Breasts, Psychosocial Well-being, Sexual Well-being, and Physical Well-being Chest in patients undergoing mastectomy alone versus mastectomy with reconstruction (26). While BREAST-Q outcomes following BCT are not as well established, Satisfaction with Breasts scores after BCT with various incision techniques have been reported, along with findings of higher scores associated with lower quantities of resected tissue and scores associated with BCT lower than reconstruction yet higher than mastectomy alone (20, 27-29).…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…In one of the earliest studies using the BREAST-Q to examine the differences in PROs between women undergoing mastectomy alone versus reconstruction, Eltahir et al demonstrated lower BREAST-Q scores for Satisfaction with Breasts, Psychosocial Well-being, and Sexual Well-being in women after mastectomy alone versus mastectomy with reconstruction (23). These findings have been replicated in multiple subsequent studies (19, 20, 24, 25), including a prospective study by Chao et al that demonstrated lower Satisfaction with Breasts, Psychosocial Well-being, Sexual Well-being, and Physical Well-being Chest in patients undergoing mastectomy alone versus mastectomy with reconstruction (26). While BREAST-Q outcomes following BCT are not as well established, Satisfaction with Breasts scores after BCT with various incision techniques have been reported, along with findings of higher scores associated with lower quantities of resected tissue and scores associated with BCT lower than reconstruction yet higher than mastectomy alone (20, 27-29).…”
Section: Discussionmentioning
confidence: 75%
“…In the literature, patients undergoing mastectomy alone have been shown to have lower BREAST-Q scores for all four pre-operative scales: Satisfaction with Breasts, Psychosocial Well-being, Sexual Well-being, and Physical Well-being, when compared to women after reconstruction (19, 20, 23-26). In the data published by Ng et al, Psychosocial Well-being is not less than 0.5 standard deviations below the norm (19).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that breast reconstruction and the associated improvement in body image positively impact health-related quality of life in women after mastectomy [14]. Although reconstruction can be carried out either at the time of mastectomy (“immediate”) or at a later time (“delayed”), immediate reconstruction has become more commonplace, due in part to reports showing superior overall aesthetic outcomes, higher levels of psychosocial well-being post-mastectomy, and lower costs, compared with delayed procedures [512].…”
Section: Introductionmentioning
confidence: 99%
“…They found QOL scores consistently deteriorated at multiple time points following mastectomy as compared to reconstructed patients. Interestingly, lower preoperative scores were found in the delayed reconstruction group compared to immediate group, with merging of scores seen at 9 months postoperatively in all QOL domains once breast reconstruction was performed . Zhong et al similarly found that patients who underwent delayed reconstruction compared with immediate reconstruction had significantly lower satisfaction with their breasts and psychosocial function; however, breast reconstruction appeared to help delayed reconstructed patients reach levels of satisfaction and psychosocial well‐being similar to the immediate reconstruction group after surgery .…”
Section: Introductionmentioning
confidence: 98%